Concentrations of alprazolam in blood from impaired drivers and forensic autopsies were not much different but showed a high prevalence of co-ingested illicit drugs. (March 2013) - Jones, Alan Wayne; Holmgren, Anita
Alprazolam is a benzodiazepine anxiolytic widely prescribed for treatment of panic-disorder and social phobias, although this medication is also subject to abuse. In this paper, the concentrations of alprazolam in venous blood samples from impaired drivers were compared with femoral blood samples from forensic autopsies classified as intoxication or other causes of death (e.g. natural, trauma). After liquid–liquid extraction ( n -butyl acetate) alprazolam was determined in blood by capillary gas chromatography with a nitrogen–phosphorous detector. The mean (median) and range of alprazolam concentrations in blood from impaired drivers ( n = 773) were 0.08 mg/L (0.05 mg/L) and 0.02–3.9 mg/L, respectively. Many traffic offenders had co-ingested ethanol (13%), amphetamine (46%), cannabis (32%), or heroin (14%), as well as other drugs. In deaths attributed to drug intoxication, the mean (median) and range of alprazolam concentrations in blood ( n = 438) were 0.10 mg/L (0.06 mg/L) and 0.02–1.6 mg/L, respectively, which were not much different from other causes of death ( n = 278); 0.08 mg/L (0.05 mg/L) and 0.02–0.9 mg/L. Median concentrations of alprazolam in blood from living and deceased persons did not seem to depend on the number of co-ingested substances. The result of this pharmacoepidemiological study suggests that alprazolam is a fairly innocent drug when used as monotherapy, but toxicity problems arise when co-ingested with illicit drugs and/or psychoactive medication.